Additional gastroduodenal stent placement: retrospective evaluation of 68 consecutive patients with malignant gastroduodenal obstruction. (October 2013) - Kang, Min Kyoung; Song, Ho-Young; Kim, Jong Woo; Kim, Jin Hyoung; Park, Jung-Hoon; Na, Han Kyu; Lee, Jong Jin; Oh, Se Jin
Background: Self-expandable metallic stent placement is widely used to manage malignant gastroduodenal obstructions. However, the techniques and effectiveness of additional gastroduodenal stent placement have not been evaluated until now. Purpose: To evaluate the technical feasibility, clinical effectiveness, and complications of additional gastroduodenal stent placement in patients with recurrent obstructive symptoms after primary gastroduodenal stenting. Material and Methods: We retrospectively analyzed data from 68 consecutive patients who had additional gastroduodenal stents placed for recurrent obstruction. Clinical effectiveness was assessed using technical and clinical success rates, gastric outlet obstruction score improvement after primary and additional stent placement, and complications. Results: Additional stent placement was technically successful in 66 of the 68 patients (97%) and symptomatic improvement was achieved in 58 (85%). The gastric outlet obstruction score improved after primary stent placement (0.3 to 1.4) and additional stent placement (0.2 to 1.4). Complications occurred in 12 of 68 patients (18%) and were caused by tumor overgrowth ( n = 7), stent collapse ( n = 2), food impaction ( n = 1), jaundice ( n = 1), and duodenal perforation ( n = 1). Conclusion: Additional gastroduodenal stent placement is technically feasible and clinically effective for patients with recurrent gastric outlet obstruction after stent placement.